Effect of pickling and mechanical surface treatment methods on adhesion strength of Ti oxide layer formed on Titanium alloy substrate - Izman, S.; Abdul-Kadir, Mohammed Rafiq; Anwar, Mahmood; Nazim, E. M.; Khor, E. K.; Konneh, Mohamed (2010)
Titanium alloys are commonly used in biomedical application in hard tissues replacement especially for knee and hip implants but facing huge wear debris due to continuous cyclic contact within the joints of the implants. Diamond coating is a potential solution for improving the tribological and wear properties of the implants made from this alloy. Diamond is known for having high wear resistance property and chemical vapour deposition (CVD) is one of the most promising methods for diamond coating. However, the major concern for CVD process is the poor adhesion of the diamond to the substrate material due to the large mismatch of coefficient of thermal expansion (CTE) properties between the two. A suitable interlayer material can be introduced to reduce the gap of CTE differences by oxidation process. In this study, the effect of pickling temperature and mechanical surface treatment methods on the adhesion strength of Ti oxide interlayer prior to diamond coating were investigated. Besides, the thickness of oxide layer and surface morphology were also evaluated. Experiments were carried out on Ti6Al4V substrate by varying the surface treatment pickling temperature from 25°C to 50°C. In mechanical surface treatment, all samples were ground using #220 to #1200 grits and followed with polishing using alumina paste. After the surface treatment process, all the substrates underwent thermal oxidation for 25 hours at 900°C. The results showed that the adhesion strength of oxide layer increases with the increasing of pickling temperature. Mechanical surface pretreatment provides better adhesion of oxide layer than chemical pretreatment (pickling process). However, the adhesion strength decreases with the increases of oxide layer thickness.